Synthesis and ethylene trimerisation capability of new chromium(II) and chromium(III) heteroscorpionate complexes. - Kilpatrick, A; Kulangara, S; Cushion, MG; Duchateau, R; Mountford, P (2010)
Reaction of (Me(2)pz)(2)CHSiMe(2)N(H)R (R = (i)Pr or Ph) or (Me(2)pz)(2)CHSiMe(2)NMe(2) with CrCl(3)(THF)(3) or CrCl(2)(THF)(2) gave Cr{(Me(2)pz)(2)CHSiMe(2)NR(1)R(2)}Cl(3) (R(1) = H, R(2) = (i)Pr (10) or Ph (11); R(1) = R(2) = Me (15)) or Cr{(Me(2)pz)(2)CHSiMe(2)NR(1)R(2)}Cl(2)(THF) (R(1) = H, R(2) = (i)Pr (12) or Ph (13); R(1) = R(2) = Me (16)), respectively. Compounds 10 and 11 were crystallographically characterized and the magnetic behaviour of all the new compounds was evaluated using SQUID magnetometry. Reaction of CrCl(3)(THF)(3) with Li{C(Me(2)pz)(3)}(THF) gave the zwitterionic complex Cr{C(Me(2)pz)(3)}Cl(2)(THF) (17) containing an apical carbanion. Reaction of the analogous phenol-based ligand (Me(2)pz)(2)CHArOH (ArO = 2-O-3,5-C(6)H(2)(t)Bu(2)) with CrCl(3)(THF)(3) gave Cr{(Me(2)pz)(2)CHArOH}Cl(3) (19) whereas the corresponding reaction with CrCl(2)(THF)(2) unexpectedly gave the Cr(III) phenolate derivative Cr{(Me(2)pz)(2)CHArO}Cl(2)(THF) (20) which could also be prepared from CrCl(3)(THF)(3) and the sodiated ligand [Na{(Me(2)pz)(2)CHArO}(THF)](2). Reaction of the corresponding ether (Me(2)pz)(2)CHArOMe with CrCl(3)(THF)(3) or CrCl(2)(THF)(2) gave Cr{(Me(2)pz)(2)CHArOMe}Cl(3) (23) and Cr{(Me(2)pz)(2)CHArOMe}Cl(2)(THF) (24), respectively. The catalytic performance in ethylene oligomerisation/polymerisation of all of the new Cr(II) and Cr(III) complexes was evaluated. Most of the complexes showed high activity, but produced a Schultz-Flory distribution of alpha-olefins. Compound 23 had an exceptionally low alpha-value of 0.37 and showed a preference for 1-hexene and 1-octene formation. While replacing a secondary amine (10-13) for a tertiary amine (15-16) resulted in loss of catalytic activity, replacing a phenol (19) for an anisole (23) group afforded a more selective and more active catalyst. Changing from MAO to DIBAL-O as cocatalyst induced a switch in selectivity to ethylene polymerisation.